Giant Mesenteric Lipoblastoma in an Infant: Case Report and Review of Literature - Haarini Sundar; Priyanka Hegde; Arun Kumar Loganathan (Wolters Kluwer Medknow Publications, 2024)
Abdominal lipoblastoma is a rare tumor composed of embryonic fat. Mesenteric involvement is rarer, with only five cases reported in infants. We report a case of a 10-month-old infant with a lipomatous tumor arising from the ileal mesentery. Primary resection was done, and histopathology was suggestive of a lipoblastoma. The child is well in follow-up with no evidence of recurrence.